Impact of Three Different Serum Sources on Functional Properties of Equine Mesenchymal Stromal Cells - Pezzanite, Lynn; Chow, Lyndah; Griffenhagen, Gregg; Dow, Steven; Goodrich, Laurie (Frontiers in Veterinary Science, 2021)
Culture and expansion of equine mesenchymal stromal cells (MSC) is routinely performed using fetal bovine serum (FBS) as a source of growth factors, nutrients and extracellular matrix proteins. However, the desire to minimize introduction of xenogeneic bovine proteins or pathogens and to standardize cellular products intended for clinical application has driven evaluation of alternatives to FBS. Replacement of FBS in culture for several days before administration has been proposed to reduce antigenicity and potentially prolong survival after injection. However, the functional consequences of MSC culture in different serum types have not been fully evaluated. The objective of this study was to compare the immunomodulatory and antibacterial properties of MSC cultured in three serum sources: FBS, autologous or allogeneic equine serum. We hypothesized that continuous culture in FBS would generate MSC with improved functionality compared to equine serum and that there would not be important differences between MSC cultured in autologous versus allogeneic equine serum. To address these questions, MSC from three healthy donor horses were expanded in medium with FBS, then switched to culture in FBS, autologous, or allogeneic equine serum for 72h. The impact of this 72h culture period in different sera on cell viability, cell doubling time, cell morphology, bactericidal capability, chondrogenic differentiation, and production of cytokines and antimicrobial peptides was assessed. Altering serum source did not affect cell viability or morphology. However, cells cultured in FBS had shorter cell doubling times and secreted more IL-4, IL-5, IL-17, RANTES, GM-CSF, FGF-2, Eotaxin, and antimicrobial peptide cathelicidin/LL-37 than cells cultured in either source of equine serum. Cells cultured in FBS also exhibited greater spontaneous bactericidal activity. Notably, significant differences in any of these parameters were not observed when autologous versus allogeneic equine serum was used for cell culture. Chondrogenic differentiation was not different between different serum sources. These results indicate that MSC culture in FBS will generate more functional cells based on a number of parameters, and that the theoretical risks of FBS use in MSC culture should be weighed against the loss of MSC function likely to be incurred from culture in equine serum.